2014
DOI: 10.1016/j.janxdis.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Partner accommodation in posttraumatic stress disorder: Initial testing of the Significant Others’ Responses to Trauma Scale (SORTS)

Abstract: Posttraumatic stress disorder (PTSD) is associated with myriad relationship problems and psychological distress in partners of individuals with PTSD. This study sought to develop a self-report measure of partner accommodation to PTSD (i.e., ways in which partners alter their behavior in response to patient PTSD symptoms), the Significant Others' Responses to Trauma Scale (SORTS), and to investigate its reliability and construct validity in 46 treatment-seeking couples. The SORTS demonstrated strong internal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
163
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(190 citation statements)
references
References 42 publications
(56 reference statements)
13
163
4
Order By: Relevance
“…However, the use of such strategies has been negatively labeled as a maladaptive form of coping (Chakrabarti & Gill, 2002) and as partner accommodation by some authors (Fredman, Vorstenbosch, Wagner, Macdonald, & Monson, 2014). Despite the consequences for their own psychological health, participants in our study identified this coping strategy as the "easier" option for keeping the peace they want in their lives.…”
Section: Discussionmentioning
confidence: 60%
“…However, the use of such strategies has been negatively labeled as a maladaptive form of coping (Chakrabarti & Gill, 2002) and as partner accommodation by some authors (Fredman, Vorstenbosch, Wagner, Macdonald, & Monson, 2014). Despite the consequences for their own psychological health, participants in our study identified this coping strategy as the "easier" option for keeping the peace they want in their lives.…”
Section: Discussionmentioning
confidence: 60%
“…For example, partners may engage in accommodating or other treatment-interfering behavior that contributes to the dyad's relationship distress and create impediments to recovery from PTSD (Fredman, Vorstenbosch, Wagner, Macdonald, & Monson, 2014), but including partners in CBCT for PTSD helps to blunt the impact of these maladaptive partner behaviors (Fredman, Pukay-Martin, Macdonald, Wagner, Vorstenbosch, & Monson, 2015). Additionally, maladaptive relationship-based behaviors, such as poor communication, may interfere with adaptive trauma disclosure, and poor conflict management may work to maintain the symptoms of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Partner accommodation of PTSD symptoms has been reported anecdotally in the literature for the last few decades (e.g., Figley, 1989; Maloney, 1988, Verbosky & Ryan, 1988), but only recently has the construct been explored empirically. Fredman, Vorstenbosch, Wagner, Macdonald, and Monson (2014) found that scores on a newly created measure of partner accommodation of PTSD were strongly associated with partners’ perceptions of trauma survivors’ PTSD symptom severity and with additional distress in romantic partners. Moreover, greater accommodation interfered with natural symptom remission in a sample of largely female, civilian trauma survivors (Fredman et al, 2016).…”
mentioning
confidence: 97%